SUNDA-JAVA TRENCH KINEMATICS, SLAB WINDOW FORMATION AND OVERRIDING PLATE DEFORMATION SINCE THE CRETACEOUS - Whittaker J.M.; Müller R.D.; Sdrolias M.; Heine C. (My University, 2007)
The kinematics and time-dependence of back-arc extension or compression is one of the most poorly understood aspects of plate tectonics, and has nearly exclusively been studied from snapshots of present-day observations. Here we combine absolute and relative plate motions with reconstructions of now subducted ocean floor to analyse subduction kinematics and upper plate strain from geological observations since 80 Ma along the 3200 km long Sunda-Java trench, one of the largest subduction systems on Earth. Combining plate motions and slab geometries enables us to reconstruct a time-dependent slab window beneath Sundaland, formed through Wharton spreading ridge subduction. We find that upper plate advance and retreat is the main influence on upper plate strain, but subduction of large bathymetric ridges, and slab-window effects, also play a significant, and at times dominant, role. Compression in the Sundaland back-arc region can be linked to advance of the upper plate. Extension of the Sundaland back-arc region correlates with two patterns of upper plate motion, (a) retreat of the upper plate, and (b) advance of the upper plate combined with more rapid advance of the Sundaland margin due to hinge rollback. Subduction of large bathymetric ridges causes compression in the upper plate, especially Wharton Ridge subduction underneath Sumatra over the period 15–0 Ma. Our reconstructions unravel the evolving geometry of a slab window underlying the Java–South Sumatra region, and we propose that decreased mantle wedge viscosities associated with this slab-window exacerbated Palaeogene extension in the Java Sea region via active rifting, and enabled Sumatran continental extension to continue at 50–35 Ma when upper plate advance would otherwise have led to compression.
Keywords: KINEMATICS; SLAB WINDOW; SUBDUCTION; SUNDALAND; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая